Relative importance of ozone energy transfer processes in the middle and upper atmosphere - Fernandez, Rafael Pedro (2009)
The relative importance of different processes and transitions in the appearance of non-LTE populations for the fundamental levels of ozone was studied by quantifying the kinetic law of every process and transition that affect each level population. The vibrational temperatures and the relative contribution of every transition are presented as a function of altitude. The results show that the appearance of non-LTE populations for the fundamental levels is not produced by a direct imbalance between absorption and emission but as a consequence of imbalanced collisional transitions provoked by the overpopulation of O3(0 v2 0) levels. This fact confirms that the relaxation cascade drives through the bending mode ν2. © 2009 Elsevier Ltd. All rights reserved.